Anomalous Broadband Spectrum Photodetection in 2D Rhenium Disulfide Transistor. Issue 23 (4th October 2019) - Xiang, Du; Liu, Tao; Wang, Junyong; Wang, Peng; Wang, Lin; Zheng, Yue; Wang, Yanan; Gao, Jing; Ang, Kah‐Wee; Eda, Goki; Hu, Weida; Liu, Lei; et al.
Abstract: 2D transition metal dichalcogenide (TMD)‐based phototransistors generally work under photoconductive, photovoltaic, or photogating mode, in which photocarriers are generated from band‐to‐band excitation. Nevertheless, due to the relatively large bandgap, most TMD phototransistors working under these modes are restricted in visible spectrum. Here, photodetection in 2D multilayer rhenium disulfide (ReS2 ) transistor via bolometric mode, which relies on light heating induced conductance change instead of band‐to‐band photoexcitation is reported, making it possible for sub‐bandgap photon detection. The bolometric effect induced photoresponse is first revealed by an anomalous sign switching of photocurrent from positive to negative while increasing gate voltage under visible light, which is further validated by the temperature dependent electrical transport measurements. The phototransistor exhibits remarkable photoresponse under infrared regime, beyond the optical bandgap absorption edge of the ReS2 flake. Additionally, it demonstrates a low noise equivalent power, less than 5 × 10 −2 pW Hz −1/2, which is very promising for ultra‐weak light detection. Moreover, the response time is below 3 ms, nearly 3–4 orders of magnitude faster than previously reported ReS2 photodetectors. The findings promise bolometric effect as an effective photodetection mode to extend the response spectrum of large bandgap TMDs for novel and high‐performance broadband photodetectors. Abstract : The bolometric effect‐induced photoresponse in ReS2 transistor is revealed by an anomalous sign switching of photocurrent from positive to negative while increasing gate voltage under visible light, which is further validated by the temperature dependent electrical transport measurement. This enables sub‐bandgap photodetection in the infrared regime with fast response speed and low noise equivalent power.